Analisis Pendidikan Karakter Berbasis Keluarga Karya Dr. H. Amirullah Syarbini, M. Ag. - Muhammad Abdul Halim Sidiq; Rika Fausiyah (Bidayatuna, 2019)
Character is defined by good values ​​(knowing value of goodness, willing to do goodness, living in good values) which are embedded in self and behavior. Character is specific identity of a person or group of people that contain values, abilities, and persistence in facing difficulties and challenges. The phenomenon of moral/akhlaq damage that affects society has prompted the Indonesian government to implement the National Policy for National Character Development (KN-PKB). One of the realizations of this policy is the importance of character education in schools, informal (family), and non-formal (community). Character education will run effectively if it involved three insitutions namely family, school and society. Family education plays an important role because it is the family that shapes the character of a child. To formulate a model framework for character education in the family it can be conceptualized through an educational approach system. If the term system is linked with education (education system), it can contain the meaning "a unitary component consisting of educational elements that are interconnected with one another to achieve educational goals." In a system there are elements, parts, or components that are interrelated and tidy, and the mechanism is interconnected in one unit, all of which are aimed at achieving one goal. The contents of the character education model framework include components: objectives, educators, students, materials, methods, tools, programs, and evaluations